Solve for y -28=4(y-2)-6y

Math
-28=4(y-2)-6y
Rewrite the equation as 4(y-2)-6y=-28.
4(y-2)-6y=-28
Simplify 4(y-2)-6y.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
4y+4⋅-2-6y=-28
Multiply 4 by -2.
4y-8-6y=-28
4y-8-6y=-28
Subtract 6y from 4y.
-2y-8=-28
-2y-8=-28
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 8 to both sides of the equation.
-2y=-28+8
Add -28 and 8.
-2y=-20
-2y=-20
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2y=-20 by -2.
-2y-2=-20-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2y-2=-20-2
Divide y by 1.
y=-20-2
y=-20-2
Divide -20 by -2.
y=10
y=10
Solve for y -28=4(y-2)-6y

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top